Menstrual management: a neglected aspect of hygiene interventions. Issue 4 (29th July 2014) - H. Parker, Alison; A. Smith, Jen; Verdemato, Tania; Cooke, Jeanette; Webster, James; C. Carter, Richard
Abstract : Purpose: – Effective menstrual management is essential for the mental and physical well being of women. However, many women in low-income countries lack access to the materials and facilities required. They are thus restricted in their activities whilst menstruating thus compromising their education, income and domestic responsibilities. The paper aims to discuss these issues. Design/methodology/approach: – This study describes the menstrual management challenges faced by women in an emergency situation in Uganda. Totally, 50 interviews and focus group discussions were conducted with women from villages, internally displaced person (IDP) camps and schools so that the menstrual management of the host population could be compared with the IDPs. Findings: – This study showed that in IDP camps there was a significant lack of materials including soap, underpants and absorbing cloth, and facilities like latrines and bathing shelters. As a consequence women in IDP camps suffer with poor health and diminished dignity. There is also a lack of education about menstruation and reproductive health and practices are strongly influenced by cultural taboos. Originality/value: – This is the first time that the menstrual management of women in IDP or refugee camps has been studied.